4w+4=6w+14

Simple and best practice solution for 4w+4=6w+14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4w+4=6w+14 equation:


Simplifying
4w + 4 = 6w + 14

Reorder the terms:
4 + 4w = 6w + 14

Reorder the terms:
4 + 4w = 14 + 6w

Solving
4 + 4w = 14 + 6w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-6w' to each side of the equation.
4 + 4w + -6w = 14 + 6w + -6w

Combine like terms: 4w + -6w = -2w
4 + -2w = 14 + 6w + -6w

Combine like terms: 6w + -6w = 0
4 + -2w = 14 + 0
4 + -2w = 14

Add '-4' to each side of the equation.
4 + -4 + -2w = 14 + -4

Combine like terms: 4 + -4 = 0
0 + -2w = 14 + -4
-2w = 14 + -4

Combine like terms: 14 + -4 = 10
-2w = 10

Divide each side by '-2'.
w = -5

Simplifying
w = -5

See similar equations:

| 5(7p-5)-[2(2p-3)+4]= | | 60-3(9-5)3= | | In(x)+In(x-2)=In(3) | | 5-9-7-1= | | 3x(-2x-7)-2y=9 | | 12-2y=8y+4 | | -6(2y-1)=3.6 | | 25.0139-7.481x=-1.1(x-8) | | 4x=15-5y | | -9p+21+16p=5(p+4)+3 | | 2x-11=38+9x | | -2m-6+8m=-4m-2+10m | | 6.5(1+0.495*1.2)=5.114+4.3*1.2 | | 3p+3(p+2)=6p+2 | | 6.5(1+0.945*1.2)=5.114+4.3*1.2 | | -2z-9=-2z-10+1 | | 6t-9=3(2t-4)+3 | | 4x+2(4+x)=3(2+5x) | | 618.5172=2*3.14*24.01+2*3.14*4.9*h | | 3.6x-1.2=.7(10-x) | | 6.5(1+0.495x)=5.114+4.3x | | 19694.08=2*3.14*196+2*3.14*14*h | | .3x=1.2+2.3x | | 64d^5-32d^2= | | 6x+1.5=4x-3 | | 0.4(x-10)+0.6x=1 | | Y+(3-5)=12 | | (5z+3)(8+z)=0 | | 7sec(x)=7 | | 33.33t=-.25 | | -16-3c=5c | | 8343.8592=2*3.14*17.64+2*3.14*4.2*h |

Equations solver categories